"Music Makes My Old Heart Beat": A Randomised Controlled Study on the Benefits of the Use of Music in Comprehensive Care for Institutionalised Older Adults. Issue 1 (23rd August 2020) - Castillejos, Carolina; Godoy‐Izquierdo, Débora
Abstract : Background: Research on the therapeutic use of music is growing, but the lack of experimental rigour and outcomes diversity has impeded researchers from obtaining clear evidence of the multiple benefits of music interventions in older adults. We explored the outcomes of a music‐complemented intervention integrated into the therapeutic activities of institutionalised elderly people. Methods: A randomised controlled study with baseline, post‐intervention, and 2‐week follow‐up measures was carried out with 50 residents in a caring institution. Several indicators of physical health, cognitive functioning, emotional well‐being, pain, and happiness were assessed at all phases. Results: Mixed factorial ANOVAs showed a positive impact of the music intervention on the outcomes in the intervention group (effect sizes up to .78) compared to the stability in the control (waiting list) group. Notably, the benefits seemed to be temporary, as they decreased progressively after the discontinuation of the intervention. Conclusions: This study demonstrates the effects of a planned music‐based intervention on several health‐ and well‐being‐related outcomes and has important applications regarding the use of music as a complement in therapeutic interventions with elderly people. The implementation of music therapy within the comprehensive care of institutionalised people must be maintained over time for the effects to be durable.